90.6k views
2 votes
Y-3x=3 and x-2y=4 using elimination method​

2 Answers

3 votes

Answer:

x = -2

y = -3

Explanation:


y-3x=3--------(1) \\ x-2y=4 --------(2)\\ -3x +y =3 ----------(1)\\x-2y =4-----------(2)\\Multiply -equation(1)-by-the-coefficient-of x -in-equation(2)\\Multiply -equation(2)-by-the-coefficient-of x -in-equation(1)\\ -3x +y =3 ----------(1)* 1\\x-2y =4-----------(2)* -3\\\\-3x+y = 3 -----(3)\\-3x +6y = -12----(4)\\Subtract -equation(4)-from-equation(3)\\-5y =15\\(-5y)/(-5) =(15)/(-5) \\y = -3\\


Substitute ; -3 -for;y -in -equation (1) or (2)\\-3x +y =3 ----------(1)\\-3x + (-3)=3\\-3x-3 =3\\-3x= 3+3\\-3x=9\\(-3x)/(-3) = (9)/(3) \\x = -2

User Jazb
by
5.5k points
5 votes

Answer:

x = -2, y = -3

Explanation:

y - 3x = 3

x - 2y = 4

-3x + y = 3

x - 2y = 4

-6x + 2y = 6

x - 2y = 4

Add the equations.

-5x = 10

x = -2

Substitute -2 for x in the first original equation and solve for y.

y - 3x = 3

y - 3(-2) = 3

y + 6 = 3

y = -3

Answer: x = -2, y = -3

User Rushi Soni
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.